2015
DOI: 10.1177/0190272515607493
|View full text |Cite
|
Sign up to set email alerts
|

Using Identity Processes to Understand Persistent Inequality in Parenting

Abstract: Despite growing acceptance of a ''new fatherhood'' urging fathers to be engaged in family life, men's relative contributions to housework and child care have remained largely stagnant over the past twenty years. Using data from in-depth interviews, we describe how identity processes may contribute to this persistent inequality in parenting. We propose that the specificity of men's identity standards for the father role is related to role-relevant behavior, and that the vague expectations many associate with ''… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 31 publications
4
24
0
Order By: Relevance
“…By reading and re-reading our summaries in various groupings, important patterns began to emerge. As discussed in previous work (Collett et al 2015), we discovered that men's interpretations of identity meanings varied in clarity, and those men with more well-developed understandings of who they aspired to be as fathers contributed more and displayed greater commitment to their families and fatherhood. We investigated the sources of specificity and found that diffuse interpretations of what it means to be a father were common among men who lack a father figure or who use their fathers as negative role models (e.g., men who want to be the person their father was not).…”
Section: Qualitative Analysissupporting
confidence: 51%
See 3 more Smart Citations
“…By reading and re-reading our summaries in various groupings, important patterns began to emerge. As discussed in previous work (Collett et al 2015), we discovered that men's interpretations of identity meanings varied in clarity, and those men with more well-developed understandings of who they aspired to be as fathers contributed more and displayed greater commitment to their families and fatherhood. We investigated the sources of specificity and found that diffuse interpretations of what it means to be a father were common among men who lack a father figure or who use their fathers as negative role models (e.g., men who want to be the person their father was not).…”
Section: Qualitative Analysissupporting
confidence: 51%
“…If they see consistency between the way that others see them, based on reflected appraisals (Cooley 1902), and their identity standard, they experience identity confirmation. This results in positive emotions and self-perceptions and may enhance a man's commitment to the identity (Collett et al 2015). Any perceived mismatch, on the other hand, indicates self-discrepancy, generates negative emotion, and will either prompt increased efforts at involvement or lead a father to alter or abandon the identity either cognitively or behaviorally (Burke and Harrod 2005;Cast and Cantwell 2007).…”
Section: The 'Good Father'mentioning
confidence: 99%
See 2 more Smart Citations
“…In the epilogue to the 2016 edition, Coontz observed that "heterosexual men are now in the midst of their own gender revolution" (p. 382). The ideology of the "new father" is one who is nurturing and emotionally engaged with his child (Collett, Vercel, & Boykin, 2015). Although fathers today are more involved in their children's day-to-day caretaking activities than in previous cohorts (Marsiglio, Amato, Day, & Lamb, 2000), Coontz observed that the ideology of the traditional family is still prevalent.…”
Section: The New Fatherhoodmentioning
confidence: 99%